The house I loved [compact disc, unabridged] - Rosnay, Tatiana de, 1961- (Macmillan Audio, 2012)
Determined to protect her historical family home from Napoleon's orders to renovate 1860s Paris, Rose Bazelet establishes a defense in the basement of her house on rue Childebert and records her experiences in letters to her late husband, a process that helps her come to terms with a decades-old secret.